Study on the algae of Haringet stream being polluted by pre-treated sewage of Elazig City (Turkey) - Sen, B.; Ozrenk, F.; Alp, M. T.; Caglar, M.; Pala, G. (Int Phycological Soc, 1997)
[Abstract Not Available]